Determinan Minat Mahasiswa Menggunakan QRIS sebagai Alat Pembayaran Digital (Studi pada Mahasiswa GENBI Bengkulu) - Wulandari, Ayu Dwi; Sunarto, Andang; Afrianty, Nonie (Universitas Batanghari Jambi, 2024)
The aim of this research is to analyze the factors that influence GENBI Bengkulu students' interest in using QRIS as a digital payment tool. The type of research used was an ex post facto quantitative method with a proportional sampling technique and the results obtained were 86 samples from a total of 200 existing populations. The data analysis technique uses factor analysis calculations using the SPSS program with the Bartlett's Test of Spherecity analysis technique. The research results showed that 3 factors were obtained which were factors that influenced GENBI Bengkulu students' interest in using QRIS, namely financial literacy, ease of use, and benefits. The cumulative percentage of variance from the extracted factors is 68.22%, which means that the results of the research formed are able to explain the factors that influence GENBI Bengkulu students' interest in using QRIS, and the most dominant factor in this research is the financial literacy factor.